ChemInform Abstract: Accelerated Zincations for an Efficient and Mild Functionalization of Aromatics and Heterocycles. Issue 32 (18th July 2013) - Unsinn, Andreas; Wunderlich, Stefan H.; Knochel, Paul
Abstract An improved protocol for the zincation and the subsequent reaction with different substituted electrophiles is presented.